Factors affecting decision making for cassava as a commercial of the people in Nan District, LuangPrabang Province. - SAYVISITH, Souliyo (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study of the Factors affecting decision making for cassava as a commercial of the people in Nan District, LuangPrabang Province, is aimed at studying the problems and obstacles and the factors affecting the decision to choose to grow cassavaes as a product of the people of Nan District, LuangPrabang Province, using analysis by the Logit Model with the Maximum Likelihood Estimate method. The results of the study found that: in the people's cassava cultivation, there will be problems related to the cost of cassava cultivation, especially the problem of high prices of cassava varieties, high labor wages, high prices of equipment for planting and harvesting, and high prices of cassava fertilizer, which is a moderate problem; as for water supply issues, experience in planting, labor in planting, quality of produce, period of time to harvest produce, storage of produce, and damage to produce are only minor problems. As for the obstacles in the cultivation of the people's potatoes, the most common obstacles are the distribution of the people's cassava products, such as: economic depression, and when there are more cassava growers, it will become an obstacle to the distribution of the people's cassava products at a moderate level; As for obstacles caused by weather or natural disasters, soil quality, weeds cassava fields, cassava diseases, pests, and transportation of produce to distribution points, there are only minor obstacles. For the factors that affect the choice of people to grow cassavas in Nan District, LuangPrabang province include: the number of dependent members in the household, experience in growing cassavas, planting cassavas can be grown to create a source of income or additional income, the presence of a market to support the distribution of produce and a group of people who grow cassavas for support, the level of education of the head of the household, the number of workers in the household, the total cost of planting, receiving promotion and support from the public sector and receiving training to grow cassavas from the public sector, which is statistically significant 0.1, 0.0 5 and 0.01 respectively.